The Potential of Turmeric Rhizome Extract in the Preparation of Cosmetic Creams and Lotions: A Systematic Literature Review - Daila Ardiswina Pondini; Eka Helmy Rosyadi; Ghofaro Nurul Azzahro; Irdiyani Fariha; Pitaloka, Lola; Muhammad Reza Akbar; Nia Yuniarsih (HM Publisher, 2023)
Turmeric (Curcuma longa) is one of the spices that have been used traditionally in medicine and beauty in various cultures for centuries. The utilization of turmeric rhizome as a cosmetic component lotion or cream is believed to be able to enhance the efficacy of these cosmetics. This study aimed to describe the potential of turmeric rhizome extract in cosmetic preparations and lotion. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of turmeric in cosmetics. The search was performed using the terms: (1)